The New Art. - Campbell, Robin; Lynton, Norbert; Seymour, Anne; Arts Council of Great Britain, London (London : Hayward Gallery, 1972)
Arnatt, Keith ; Art & Language ; Burgin, Victor ; Craig-Martin, Michael ; Dye, David ; Flanagan, Barry ; Fulton, Hamish ; Gilbert & George ; Hilliard, John ; Long, Richard ; Milow, Keith ; Newman, Gerald ; Stezaker, John ; Tremlett, David
biografie
The New Art, Hayward Gallery, London, August 17 - September 24, 1972
Engels
boek
Keywords: Arnatt, Keith; Art & Language; Austin, John; Burgin, Victor; Craig-Martin, Michael; Dye, David; Flanagan, Barry; Gilbert & George; Hilliard, John; Long, Richard; Milow, Keith; Newman, Gerald; Stezaker, John; Tremlett, David